Persepsi dan Interaksi Masyarakat Desa Wawona terhadap Monyet Hitam Sulawesi - Michael Rantung; Johny S. Tasirin; Reynold P. Kainde; Lyndon Pangemanan (COCOS, 2015)
ABSTRACTPercetion and Interaction of Wawona Wawona Rural Communities to Sulawesi Black MonkeysSulawesi is the largest area in the region which is biogeography walacea a meeting location flora and fauna between the Indo-Malaysia and Australasia (Lee et al, 2001). In North Sulawesi are black monkeys Sulawesi (Macaca nigra). Currently, the existence of black monkeys Sulawesi experienced survival in nature. The main factor is the high intensity of the interference that comes from outside the region, either in the form of disturbance to habitat conversion of forest land into agricultural land as well as on the black monkeys Sulawesi itself in the form of hunting.Wawona village is the village directly adjacent to the Wildlife Manembonembo. The total area of the village of Wawona is 20.5 km2, or 19.01% of the area of the District Tatapaan. There are still many people who capture animals Village Wawona (34%). Although only 6% of the people who catch monkeys Sulawesi black, but most people still eat meat Sulawesi black monkey. Most of the community looked at the forest just as a place to store water (53%) and prevention of flooding (23%) only 9% who considered that forests are important for the survival of animals that includes monkeys Sulawesi black.